Uso de macroalgas para avaliação da Poluição orgânica no Rio Preto, noroeste do estado de São Paulo. - Necchi Jnr, O.; Branco, H. Z.; Dip, M. R. (My University, 1994)
The Preto River, located in the northwest of São Paulo State, receives a total wastewater load of 15.150 kg DBO day-1, from which 13.685 kg DBO day-1 (90.5%) corresponds to domestic sewage, and the city of São José do Rio Preto contributes with 12.400 kg DBO day-1 (90% of domestic sewage). During the period from August 1990 through January 1991, monthly sampling was carried out to evaluate the use of macroalgae as bioindicator of organic pollution. Five sampling sites were established along the main river and the following variables were analised: temperature, conductance, turbidity, dissolved oxygen, BOD, COD, total and fecal coliforms, and composition and abundance of macroalgal communities. Data were submitted to analysis of variance, correlation coefficient, cluster analysis (four different approaches) and converted to biological indices (species deficit, relative pollution, saprobity, diversity and uniformity indices). A wide range in water quality was found (particularly for conductance, oxygen, BOD and COD) among the sampling sites, which were classified into three groups (polluted, moderately polluted and unpolluted/weakly polluted). As regards the occurrence and abundance of macroalgae the Rhodophyta were found only in unpolluted or weakly polluted sites, whereas Cyanophyta occurred mostly under high pollution load; the Chlorophyta species were observed under a wide range of conditions. Among the biological indices, saprobity was the most sensitive and correlated to all water variables and the other indices. Cluster analyses showed that the composition of macroalgal communities was consistent with the levels of organic pollution in the Preto River.
Use of macroalgae for the evaluation of organic pollution in the Preto river, northwest of São Paulo State
Keywords: fresh water; alga; analysis of variance; Brazil; water pollutant; Algae; Analysis of Variance; English Abstract; Fresh Water; Support, Non-U.S. Gov't; Water Pollutants, Chemical